2003
DOI: 10.1021/la020743t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additives on Oxygen Reduction Kinetics at the Interface between Platinum and Perfluorinated Ionomer

Abstract: The oxygen reduction reaction (ORR) at platinum electrodes covered with perfluorosulfonated ionomer film was studied in 0.05 mol dm-3 H2SO4 in the presence of various kinds of ammonium ions. Ammonium ion derivatives (R4N)2SO4 (R = H, CH3) and (R4N)HSO4 (R = C2H5, C3H7, and C4H9) were added with various amounts in the solution. The electrochemical measurements of ORR were performed to evaluate both charge transfer and diffusion kinetics of oxygen reduction at the Nafion film covered platinum rotating disk elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 11 publications
0
29
1
Order By: Relevance
“…The assumptions of the model are as follows: (1) the contaminant is dilute relative to the humid single phase gas stream; (2) only the x (along the channel) and the z (perpendicular to the membrane) directions are important; (3) negligible pressure drop along the channel; (4) isothermal conditions exist; (5) the effective diffusion coefficients in the porous GDL, ionomer, and membrane can be written using the MacMullin number; [30][31][32] (6) constant physical and transport parameters; (7) ideal gas law; (8) well-developed laminar flow in the channel; (9) the Butler-Volmer equation can be used to describe the cathode reaction with the Tafel assumption; (10) the rate of contamination is governed by the rate of mass transport of contaminant A by diffusion in liquid water, gas, or solid ionomer depending on the species and the saturation of the GDL, CL, or membrane; 3,26,33 (11) Langmuir adsorption isotherms apply for the adsorption behavior; (12) gas-phase transport of contaminants in the channel (although the contaminant is fed in the liquid state, it is nebulized prior to entering the cell in the experimental apparatus; thus, although salt cations are not present in the gaseous phase, their average bulk concentration in suspended droplets can be approximated as diluted by the gas stream and they can Journal of The Electrochemical Society, 161 (14) F1375-F1388 (2014) F1377 be transported with the gas stream (i.e., aerosol)) a ; (13) no interaction between contamination mechanisms; (14) neglect of migration and convection; (15) contaminant concentrations are equal in the liquid and gas phases because the concentration is very low; and (16) linear distributions of contaminants in the electrode and membrane.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The assumptions of the model are as follows: (1) the contaminant is dilute relative to the humid single phase gas stream; (2) only the x (along the channel) and the z (perpendicular to the membrane) directions are important; (3) negligible pressure drop along the channel; (4) isothermal conditions exist; (5) the effective diffusion coefficients in the porous GDL, ionomer, and membrane can be written using the MacMullin number; [30][31][32] (6) constant physical and transport parameters; (7) ideal gas law; (8) well-developed laminar flow in the channel; (9) the Butler-Volmer equation can be used to describe the cathode reaction with the Tafel assumption; (10) the rate of contamination is governed by the rate of mass transport of contaminant A by diffusion in liquid water, gas, or solid ionomer depending on the species and the saturation of the GDL, CL, or membrane; 3,26,33 (11) Langmuir adsorption isotherms apply for the adsorption behavior; (12) gas-phase transport of contaminants in the channel (although the contaminant is fed in the liquid state, it is nebulized prior to entering the cell in the experimental apparatus; thus, although salt cations are not present in the gaseous phase, their average bulk concentration in suspended droplets can be approximated as diluted by the gas stream and they can Journal of The Electrochemical Society, 161 (14) F1375-F1388 (2014) F1377 be transported with the gas stream (i.e., aerosol)) a ; (13) no interaction between contamination mechanisms; (14) neglect of migration and convection; (15) contaminant concentrations are equal in the liquid and gas phases because the concentration is very low; and (16) linear distributions of contaminants in the electrode and membrane.…”
Section: Modelmentioning
confidence: 99%
“…Many previous studies for contamination [3][4][5][6][7][8][9][10][11][12][13] in PEMFCs have shown the sensitivity of performance to low levels of contamination. For example, cation leachates from gaskets or seals, from NH 3 in the fuel, or from catalyst metals 3-9 are well known contaminants of the membrane through an ion-exchange mechanism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We ignore secondary effects such as changes in transport rates of reactants through the catalyst layer, 40,41 increase in peroxide production [40][41][42] or changes in Tafel slopes [43][44][45] as has been reported previously. Also, ion exchange with the membrane can lead to highly non-linear effects at high currents or significant cation exchange.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Membrane conductivities for pristine and ε-caprolactam-exchanged NRE211 membranes were determined at different relative humidity (RH) (i.e., 10,20,30,40,50,60,70,80,90, and 95%) by applying DC currents at a cell temperature of 80…”
Section: Methodsmentioning
confidence: 99%